2016
DOI: 10.3892/or.2016.4981
|View full text |Cite
|
Sign up to set email alerts
|

Next generation deep sequencing identified a novel lncRNA n375709 associated with paclitaxel resistance in nasopharyngeal carcinoma

Abstract: Paclitaxel chemoresistance restricts the therapeutic efficacy and prognosis of patients with nasopharyngeal carcinoma (NPC). Accumulating evidence suggests that aberrant expression of long non-coding RNAs (lncRNAs) contributes to cancer progression. Therefore, we aimed to identify lncRNAs associated with paclitaxel resistance in NPC. First, paclitaxel-resistant CNE-2 cells (CNE-2-Pr) were successfully established and confirmed to be 33.26±8.70 times more resistant than parental CNE-2 cells. Then, differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…23 Additionally, n375709, a newly identified lncRNA, was documented to be highly expressed in NPC cells and implicated in the regulation of NPC paclitaxel resistance. 24 However, the roles of NEAT1 and its underlying mechanisms in cisplatin resistance remain unclear. In our study, we confirmed the upregulation of NEAT1 in NPC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…23 Additionally, n375709, a newly identified lncRNA, was documented to be highly expressed in NPC cells and implicated in the regulation of NPC paclitaxel resistance. 24 However, the roles of NEAT1 and its underlying mechanisms in cisplatin resistance remain unclear. In our study, we confirmed the upregulation of NEAT1 in NPC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, GAS5 has raised increased attention due to its downregulation in a wide variety of malignancies, including non-small cell lung cancer (NSCLC), 16,17 breast cancer (BC), 18,19 hepatocellular carcinoma (HCC), 20,21 esophageal carcinoma (EC), 22,23 gastric cancer (GC), 24,25 colorectal cancer (CRC), 26,27 pancreatic cancer (PC), 28,29 cervical cancer (CC), 30,31 ovarian cancer (OC), 32,33 renal cell carcinoma (RCC) 34,35 (Figure 1). Clinicopathological characteristics, such as overall survival (OS), disease-free survival (DFS), distant metastasis (DM), lymph node metastasis (LNM), tumor node stage (TNM) and tumor size, are highly correlated with the level of GAS5 expression in cancers, 16,19,27,36,37 indicating that GAS5 can be a novel diagnostic and prognostic biomarker, as well as therapeutic target in many human cancers.…”
Section: Gas5 In Cancermentioning
confidence: 99%
“…8,9 Recently, Ren et al identified a novel lncRNA n375709 by next generation deep sequencing, which was overexpressed and led to paclitaxel resistance in NPC. 10 LncRNA ANRIL (CDKN2B antisense RNA 1) was located a 42-kb stretch on the chromosome 9p21, which was originally identified from familial melanoma patients with germline deletion in the INK4B-ARFINK4A gene cluster. 11,12 Subsequently, accumulating documents have indicated that ANRIL is deregulated in various malignancies, such as lung cancer, breast cancer, gastric cancer.…”
Section: Introductionmentioning
confidence: 99%